2006
DOI: 10.1152/ajpregu.00159.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-3 receptors in gastric mechanisms of cholecystokinin-induced satiety

Susan Aja

Abstract: OUR UNDERSTANDING OF THE CONTROLS of food intake has increased substantially during the last 30 years. Important in this has been the recognition of the meal as a controlled, physiologically relevant unit of energy intake. During a meal, ingested nutrients accumulate in the stomach and gradually pass to the small intestine. The gastrointestinal presence of nutrients stimulates the release of peptides and neurotransmitters that coordinate gastrointestinal secretion and motility to facilitate digestion. These ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…While parenteral 5‐HT administration has been shown to reduce meal size and duration in rats, vagotomy appears to increase this effect (Fletcher and Burton, 1985; 1986). Additionally, outcomes of studies using 5‐HT 3 receptor antagonists to influence satiety in animals and humans have generally been inconsistent, raising questions for a peripheral role of 5‐HT in food intake regulation (for review, see Aja, 2006). Indeed, most attention has been focussed on central sites of satiety actions of 5‐HT acting on 5‐HT 1 and 5‐HT 2 receptor subtypes (for review, see Atkinson, 2008).…”
Section: Intestinal Vagal Afferent Satiety Signalsmentioning
confidence: 99%
“…While parenteral 5‐HT administration has been shown to reduce meal size and duration in rats, vagotomy appears to increase this effect (Fletcher and Burton, 1985; 1986). Additionally, outcomes of studies using 5‐HT 3 receptor antagonists to influence satiety in animals and humans have generally been inconsistent, raising questions for a peripheral role of 5‐HT in food intake regulation (for review, see Aja, 2006). Indeed, most attention has been focussed on central sites of satiety actions of 5‐HT acting on 5‐HT 1 and 5‐HT 2 receptor subtypes (for review, see Atkinson, 2008).…”
Section: Intestinal Vagal Afferent Satiety Signalsmentioning
confidence: 99%
“…Distension of the stomach by a volume load is able to reduce food intake significantly 2, 3 . Exposing the small intestine to nutrients leads to release of gut peptides and neurotransmitters that induce a reduction in hunger levels and food intake 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…During the process of meal ingestion, some nutrients will already have entered the small intestine and gastric and intestinal satiety signals interact to limit meal size, 5, 8 to increase satiation and to increase satiety between meals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electrophysiological studies have shown that endogenously released and intraluminally perfused 5-HT activated vagal afferent neurons within the nodose ganglion. On the other hand, 5-HT is considered as one of the key factors that regulates food intake and mediates satiety due to its wide distribution within the GI tract[ 82 ].…”
Section: Gastric Emptying and Pancreatic Secretion: Multifactorial Phmentioning
confidence: 99%